J. MARK RAMSEYER: Second-Best Justice. The Virtues of Japanese Private Law - Dernauer, Marc (Zeitschrift für Japanisches Recht, 2016)
The University of Chicago Press, Chicago and London 2015, xii + 283 pp. (242 pp. + Notes, References & Index), ca. 50 US, ISBN: 978 0 226 28199 5